(3CKQ GdeJZjQGJ GdGLJeGYjI (B- (3GdGbJUGOjI aj GdYWGA GdJQHhj ddeYde (B( (3eMGaXI GdLfhH GdYGe GdOQGSj (B1999/2000)s - (3TMGOj, YGjOI MSfs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2003)
(3JgOa GdOQGSI Edi GdJYQa Ydi CSHGH YOe QVi GdeOQS Yf egfJg hYf ecGfJg GdELJeGYjI, hGdJYQa Ydi GdeTcdGJ GdegfjI hGdELJeGYjI GdJj jYGfj efgG GdeOQShf, hNGUI YfO ebGQfI faSg HZjQg eef jfJehf Edi GdhXGFa GdCNQi, heG jMGWhf Hg ef GMJQGe hJbOjQ JHYG dCYeGdge hQhGJHge heLGdGJ Gdfeh Gdegfj CeGege, GdCeQ GdPj jDOj Edi fhY ef GdEMHGW YfOg eeG jDKQ aj CYeGdg hEfJGLjJg hChVGYg GdegfjI(B. (3HGdEVGaI Edi eMGhdI QHW GdhVY GdGLJeGYj hGdGbJUGOj HeSJhi YWGFg hEfJGLjJg haYGdjJg(B. (3EYJeOJ GdOQGSI efgL OQGSI GdMGdI, hGSJNOeJ JbfjI GdebGHdI eY HYV GdeOQSjf heY QFjS QGHWI GdeYdejf aj eMGaXI GdLfhH hHYV GdCYVGA, HGdEVGaI Edi GdGSJeGQI(B. (3Jchf eLJeY GdOQGSI ef (B20 (3eOQSI QSejI aj eMGaXI GdLfhH, h(B73 (3eYdkeG h (B127 (3eYdeI ddeQMdJjf GdEHJOGFjI hGdeJhSWI(B. (3HjfJ GdfJGFL Cf fSHI cHjQI ef GdeYdejf ZjQ QGVjf Yf hVYge GdhXjaj dCSHGH GbJUGOjI eYjTjI hCSHGH GLJeGYjI(B. (3ceG JHjf Cf CSHGH JOghQ GdeSJhi GdJYdjej jYhO HLRA cHjQ efg Edi JbUjQ GdeYde, dcfg djS GdSHH GdhMjO, Hd jhLO CSHGH CNQi JJMed eSDhdjJgG GdEOGQI GdJQHhjI (B((3eKd YOe JhGaQ GdcJGH GdeOQSj GdLjO, GdJLgjRGJ, GdhSGFd GdJQHhjI GdVQhQjI, GdHfGA GdeOQSj GdUGdM hGdedGFe, Ch GdefGgL GdJYdjejI GdMOjKI hGdeJhGabI eY QhM GdYUQ hGdYde(B). (3CeG ajeG jNU JHQjQ GdeYde dJbUjQg HYOe EfUGag eGOjG heYfhjG, dG jYhO abW dgPG GdSHH Hd dCSHGH CNQi cKjQI aQVJgG GdXQha GdGLJeGYjI GdfGJLI Yf GdMQH GdCgdjI aj dHfGf, hYf GdUQGY GdYQHj GdESQGFjdj hEfYcGSGJg Ydi GdLfhH GddHfGfj, hEdi JbUjQ GdEOGQI GdJQHhjI aj VHW GdCehQ(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Les Facteurs Socio- Economiques; Performance professionnel; Professional performance; Social and Economic Factors; (3GdGOGA Gdegfjs; (3GdYhGed GdGLJeGYjI hGdGbJUGOjIs